Economic growth: A note on demographic and economic issues - Chris Nixon (New Zealand Institute of Economic Research (NZIER), 2004)
Understanding the relationship between economic growth and its supply side influences is fundamental to understanding the sustainability of future New Zealand real per capita growth rates. This note is primarily directed at developing a wider appreciation of the issues involved in the supply determinants of real per capita growth rates and examine the implications for New Zealand until 2010 and beyond.
Keywords: 330; Bevölkerungsentwicklung; Erwerbspersonenpotenzial; Wirtschaftswachstum; Produktivität; Neuseeland